Surgical Repair of Bile Duct Injuries Due to Cholecystectomy—An Experience from a Referral Center in Slovenia - Irena Plahuta; Špela Turk; Barbara Lovrenčič Petreski; Tomislav Magdalenić; Stojan Potrč; Arpad Ivanecz (Life, 2025)
Background: Bile duct injury (BDI) during (laparoscopic) cholecystectomy has an incidence of up to 1.5%. This retrospective study aimed to report the outcomes of surgical repair of BDI due to these procedures at a tertiary referral center. Methods: A retrospective review of patients’ records was conducted. The BDI’s clinical presentations, Strasberg classification, surgical repairs, and outcomes were reported. Results: From 2003 to 2024, 47 BDIs were identified. In total, 34.0% were recognized intraoperatively. The BDI types included Strasberg types B (2, 4.3%), C (5, 10.6%), D (11, 23.4%), E1 (4, 8.5%), E2 (12, 25.5%), E3 (5, 10.6%), E4 (3, 6.4%), and E5 (5, 10.6%). The T-tube group included 6 (12.8%) patients, the primary repair and T-tube group included 10 (21.3%) patients, and the Biliodigestive anastomosis group included 31 (65.9%) patients. The overall morbidity rate was 40.4%, the major morbidity rate was 21.3%, and the mortality rate was 4.3%. Grade A patency was achieved in 95.6% of patients. In the Biliodigestive anastomosis group, the actuarial 1-, 5- and 10-year grade A patency rates were 77.0%, 70.0%, and 70.0%, respectively. Conclusion: The rate of BDI remains stable. The outcomes of repairs in terms of complications and patency rates are comparable to those in other reports.